ANOMALIAS DENTAIS ASSOCIADAS ÀS AGENESIAS - Ribeiro, Sabrina Rocha (2011)
The objective of this retrospective study was evaluate the prevalence of anomalies in tooth position (palatal ectopic eruption of the maxillary canine, dental transposition, distal angulation of mandibular second premolars, mesial angulation of mandibular permanent second molar and infra-occlusion of deciduous molars), number (supernumerary teeth) and size (microdontia) in patients with permanent tooth agenesis, by comparing them with the rates expected for the general population; in addition, the hypothesis was tested that patients with agenesis of permanent teeth have increased prevalence of enamel hypoplasia. To that end, the sample of this study consisted of 351 patients with agenesis of at least one permanent tooth, ranging between 8 and 30 years of age and with full clinical records. The sample was collected by examining orthodontic records belonging to the archives of a professional institution of specialization in Orthodontics, a dental radiology clinic and private orthodontic practices. Study materials included panoramic and periapical view radiographs, plaster cast models, intra- and extraoral photographs and filled-out medical records. First, the reproducibility of evaluations was analyzed through the rate of concordance using the Kappa test, at a 95% confidence interval. The Chi-square test was used to compare the prevalence of agenesis and anomalies in the sample to the expected rates according to scientific literature, considering a 5% level of significance. The study also analyzed the degree of the associations using the odds ratio and the respective 95% confidence interval. The prevalence of dental agenesis in the sample, excluding third molars, was 88.6%. Of the 351 patients, 128 (36.4%) had agenesis in the maxillary arch, 108 (30.8%) in the mandibular arch, and 115 (32.8%) in both arches. A total of 52.4% had agenesis in the maxillary left hemiarch, 55.0% in the maxillary right hemiarch, 48.7% in the mandibular left hemiarch and 47.3% in the mandibular right hemiarch. With regard to the associated anomalies evaluated, 28.5% microdontia, 28.2% had enamel hipoplasia, 7.4% had palatal ectopic eruption of the canine, 6.6% had distal angulation, 4.3% infra-occlusion, 3,9% transposition of canine/premolar, 3.7% supernumerary teeth, 3.7% medial angulation, 0,6% transposition of incisive/canine, and, when compared to the general population, they were 96.1 times more likely to feature mesial angulation of the mandibular second molar; 34.6 times more likely to have distal angulation; 15,9 times more likely to show transposition of canine/premolar; 14,3 times more likely to show transposition of incisive/canine; 9 times more likely to show hipoplasia; 8,1 times more likely to show microdontia of the lateral incisor; 5,2 times more likely to have palatal ectopic eruption of the canine; and with regard to infra-occlusion, there was a lower likelihood than the general population. From the obtained results, a strong association was observed between agenesis of permanent teeth with significant dental anomalies. It was detected that permanent tooth agenesis showed an increased prevalence of enamel hypoplasia, and that agenesis and other associated anomalies are genetically interlinked.